2016
DOI: 10.1021/acs.nanolett.6b04171
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Valley Effects in Monolayer WS2 under High Magnetic Fields

Abstract: Transition-metal dichalcogenides can be easily produced as atomically thin sheets, exhibiting the possibility to optically polarize and read out the valley pseudospin of extremely stable excitonic quasiparticles present in these 2D semiconductors. Here, we investigate a monolayer of tungsten disulfide in high magnetic fields up to 30 T via photoluminescence spectroscopy at low temperatures. The valley degeneracy is lifted for all optical features, particularly for excitons, singlet and triplet trions, for whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
127
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 49 publications
21
127
2
1
Order By: Relevance
“…Strikingly, the effective g -factor of X IL is of opposite sign, with g IL  = +4 ± 0.5, indicating a different physical mechanism. Each excitonic resonance exhibits a diamagnetic shift depending on B 2 : , with e the electronic charge, the excitonic root-mean-square (RMS) radius, and the reduced mass 22 . is the deviation of the exciton’s mean transition energy for from the zero-field value.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, the effective g -factor of X IL is of opposite sign, with g IL  = +4 ± 0.5, indicating a different physical mechanism. Each excitonic resonance exhibits a diamagnetic shift depending on B 2 : , with e the electronic charge, the excitonic root-mean-square (RMS) radius, and the reduced mass 22 . is the deviation of the exciton’s mean transition energy for from the zero-field value.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing these findings with a general doping dependent valley relaxation mechanism and previous reports on exciton dynamics, we reveal the correlation between P c and physical doping. Our results demonstrate the tunable valley polarization degree under low cost and helium‐free condition, equally effective as conducted under 10 T magnetic field . We successfully enriched the understanding of valley relaxation process by electrostatic and optical doping means, which denotes an essential step toward practical valleytronic applications.…”
mentioning
confidence: 70%
“…Compared to magnetic methods, electrical/optical control of valley states are more favored for future valleytronic devices operations. As a more practical method to create population imbalance between two valleys, our approaches correspond to a 10 T magnetic field which enhances polarization degree of trion emission from negligible value to about 25% at 4.2 K . For PL without magnetic field, Cui et al reported P c = 40% at near resonance excitation (2.088 eV) and 16% at off‐resonance excitation (2.331 eV), measured at 10 K. Korn and co‐workers reported 21% for singlet trion and 34% for triplet trion with 2.15 eV laser excitation at 4.5 K .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…At monolayer thickness, TMDs can exhibit direct electronic and optical bandgaps ranging from the visible to the near-infrared. Optical spectroscopy techniques such as photoluminescence (PL) and Raman are currently the key methods used in studying TMD properties such as bandgap energy, [15,16] emission efficiency, [17][18][19] and defect density [19][20][21]. However, PL and Raman spectroscopies have limited quantum efficiency, making them unfit for high-throughput applications.…”
Section: Case Study 1 Transmission Characterization Of 2d Transitionmentioning
confidence: 99%